Preemptive antiviral therapy with entecavir can reduce acute deterioration of hepatic function following transarterial chemoembolization - Yoo, Sun Hong (Clin Mol Hepatol, 2016)
BACKGROUND/AIMS: Hepatic damage during transarterial chemoembolization (TACE) is a critical complication in patients with hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC). Apart from its role in preventing HBV reactivation, there is some evidence for the benefits of preemptive antiviral therapy in TACE. This study evaluated the effect of preemptive antiviral therapy on acute hepatic deterioration following TACE. METHODS: This retrospective observational study included a prospectively collected cohort of 108 patients with HBV-related HCC who underwent TACE between January 2007 and January 2013. Acute hepatic deterioration following TACE was evaluated. Treatment-related hepatic decompensation was defined as newly developed encephalopathy, ascites, variceal bleeding, elevation of the bilirubin level, prolongation of prothrombin time, or elevation of the Child-Pugh score by ≥2 within 2 weeks following TACE. Univariate and multivariate analyses were conducted to identify factors influencing treatment-related decompensation. Preemptive antiviral therapy involves directing prophylaxis only toward high-risk chronic hepatitis B patients in an attempt to prevent the progression of liver disease. We regarded at least 6 months as a significant duration of preemptive antiviral treatment before diagnosis of HCC. RESULTS: Of the 108 patients, 30 (27.8%) patients received preemptive antiviral therapy. Treatment-related decompensation was observed in 25 (23.1%) patients during the follow-up period. Treatment-related decompensation following TACE was observed more frequently in the nonpreemptive group than in the preemptive group (29.5% vs. 6.7%, P=0.008). In the multivariate analysis, higher serum total bilirubin (Hazard ratio [HR] =3.425, P=0.013), hypoalbuminemia (HR=3.990, P=0.015), and absence of antiviral therapy (HR=7.597, P=0.006) were significantly associated with treatment-related hepatic decompensation. CONCLUSION: Our findings suggest that preemptive antiviral therapy significantly reduces the risk of acute hepatic deterioration. Preventing hepatic deterioration during TACE by applying such a preemptive approach may facilitate the continuation of anticancer therapy and thus improve long-term outcomes.